BORED AND DRIVEN PILE TESTING IN BANGKOK SUB-SOILS - A. S. Balasubramaniam; E. Y. N. Oh; N. Phienwej (International Association of Lowland Technology, 2009)
As a necessity to support an increasing magnitude of loads from tall buildings and long span bridges, the piling practice in the Bangkok Plain has moved several phases from driven pre-cast reinforced and pre-stressed concrete piles of smaller cross sections to spun piles and large diameter bored piles. The Chao Phraya plain in which the Bangkok city is located is low-lying and consists of a broad basin filled with sedimentary soils which form alternate layers of clay, sand, and clay. The upper clay layer is soft and highly compressible followed by a stiff clay layer extending to about 20 m or so and then followed by a layer of sand. Driven piles are normally taken down to this upper sand layer. However when the demand for a higher capacity arise, these piles cannot be extended in length due to construction problems and as such bored piles are needed to be taken down to as deep as 50 to 60 m. Below the upper clay layer there are eight interconnected aquifers from which ground water is pumped from deep wells. Thus in the design of piled foundations aspects such as the negative skin friction due to pile driving as well as deep well pumping are also needed to be considered. Some of the experiences gained over a period of 30 years in the study of piled foundations in the Bangkok Plain are briefly presented in this paper.